HUBUNGAN ANTARA PENGANGGURAN DAN UPAH MINIMUM DI INDONESIA - Yuliansyah Yuliansyah (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2020)
This study aims to examine the relationship between unemployment and the minimum wage for the 2015-2020 period in Indonesia. This research was conducted with a descriptive approach. The data used in this study is secondary data from the Central Statistics Agency, namely minimum wage data and data on the number of unemployed. The result of this study is that the minimum wage affects the level of unemployment in Indonesia in that period. Except in 2020 the minimum wage does not affect unemployment.